O PAPEL MEDIADOR DOS JOGOS DIDÁTICOS NO OLHAR DE LICENCIANDOS DE CIÊNCIAS BIOLÓGICAS: UM ESTUDO NA PERSPECTIVA DA TEORIA HISTÓRICO-CULTURAL - Severo, Carol (2023)
Considering the use of didactic games in the context of Biology teaching, we found that its several benefits for learning are related, especially, to facilitation, motivation, and interaction. Thus, in the teaching of more complex areas, such as Genetics, teachers can use this type of resource to contribute to their student’s learning, through a playful and educational combination. However, considering the nature of the game, both didactic and mediating, the looks do not seem to go beyond these benefits. In this sense, the present research aims to analyze the perception of undergraduate students in Biological Sciences about the mediating role of didactic games in the protein synthesis’s teaching and learning process. As a starting point, a literature review was conducted with the scope of didactic games in Natural Sciences, which directed the study to the teacher’s formative context and the possible mediating function that the game can assume, based on Vygotsky’s theory. The research was carried out with undergraduate students from a Biological Sciences course at a public higher education institution in Rio Grande do Sul. Among the instruments used for data collection, such as questionnaires, focus groups, and observation, we highlight the use of a didactic game called “Sintetize”, elaborated by the author and her supervisor, for this study, since it was considered essential the experience of future teachers with this type of resource, for them to realize, especially, its mediating aspects in the protein synthesis’s teaching and learning process. Through the Discursive Textual Analysis and Implicative Statistics, the data were analyzed, evidencing the prevalence of the idea that teachers are the ones who mediate the teaching and learning process. On the other hand, we also evidence a variety of aspects that characterize the mediation established by didactic games, which include the true teacher’s role according to the Historical-Cultural Theory, as well as reveal that the experience with games implies the adoption of this type of resource in the classroom. In addition, the results show that the quality of materials, such as the didactical game Sintetize, promotes a playful environment, in which the students themselves design the protein synthesis process through its gameplay. In turn, the Sintetize mechanism helps to overcome the complexity of this theme, enabling students’ contact with this content from the articulation between several concepts that are often fragmented by the curriculum.